PENGENALAN INVESTASI SYARIAH KEPADA SISWA SMA MBS KI BAGUS HADIKUSUMO JAMPANG BOGOR - Toto Tohari; Yadi Nurhayadi; Fikri Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Investment is one way to utilize money in the hope of earning profits in the future. However, an understanding of investing is not always taught to high school students, but rather investing is an important skill that can help students prepare for their future. Therefore, a community service program on the introduction of investment to high school students needs to be carried out. Community service programs on introducing investment to high school students can help increase students' understanding of investing, so that they can better prepare for their future. The program can also help students build investing skills that can be useful in the future. Therefore, this community service program needs to continue to be carried out and developed in order to provide optimal benefits for high school students